Social Cohesion of Residents and Jamaah Tabligh: An Analysis of Interaction and Acceptance of Religious Traditions in Maesan, Bondowoso - Haerul Anwar; Saihan Saihan; Siti Masrohatin (Westscience Press, 2026)
The presence of Jamaah Tabligh often elicits diverse responses, ranging from acceptance to resistance, driven by differences in religious traditions and preaching methods. However, a distinct phenomenon of strong social cohesion exists in Penanggungan Village, Maesan, Bondowoso, where the group is openly welcomed by a community predominantly rooted in Nahdlatul Ulama traditions. This study analyzes how social cohesion is constructed through interaction patterns and the process of community acceptance toward Jamaah Tabligh’s religious traditions within this rural setting. Utilizing a qualitative case study, data from participatory observations, in-depth interviews, and documentation were analyzed using the interactive model by Miles, Huberman, and Saldaña. The findings reveal that social cohesion manifests through harmonious interactions, including interpersonal communication, mosque-centric activities, jawlah, regular Islamic study sessions, and civic involvement. Community acceptance of these traditions evolves gradually, facilitated by continuous social interaction, the group's profound respect for local culture, adaptive communication, and exemplary daily conduct. Addressing a gap regarding the acceptance of transnational Islamic movements in rural areas with strong local traditions, this research highlights that social cohesion and acceptance are driven by interaction quality, cultural respect, and civic engagement rather than mere preaching content, ultimately fostering grassroots religious harmony.